184 - STUDY OF USE OF HISTAMINE 2 (H2)- RECEPTOR ANTAGONISTS AND PROTON PUMP INHIBITORS (Fiep Bulletin - online, 2011)
Histamine 2 ( H2 )- receptor antagonists and Proton pump inhibitors are highly effective in the treatment of hypersecretory gastrointestinal disorders and are widely prescribed for the prevention of stress ulcer with gastrointestinal bleeding. Objective: To evaluate the prescription patterns and the appropriation of H2 blockers and omeprazole. Methods: A transversal study was conducted in three hospitals( one teaching hospital and two private non profit hospitals). The indications, as well as the type, dose of these drugs were investigated. The prescribers were asked about the reasons for prescribing these medications. Results: Among the 418 patients evaluated 229 ( 54.8%) received H2 blockers and omeprazole prescriptions. Among these 229 patients, 55.5% were male. The most common diagnoses were: malignancies (21.5%); cardiovascular diseases (11.9%); injury, poisoning and certain other consequences of external causes (9.7%); convalescence following surgery (8.3%); gastrointestinal diseases (7.5%). In 52.9% of the prescriptions the prescribers gave the reason for their prescriptions. The most common justifications were stress ulcer prophylaxis (14%); concomitant use of corticosteroids (13.2%); concomitant use of NSAIDs (8.4%); treatment of gastrointestinal diseases (7.9%). It was also evaluated the mean dose of these drugs for each age stratum. Some of the prophylactic indications did not agree with current guidelines. Educative interventions seem to be necessary to promote rational use of these drugs.
Keywords: Histamine H2 blockers; ranitidine; peptic ulcer disease; prophylaxis